On the use of model transformations for the automation of the 4SRS transition method - Azevedo, S.; Machado, R. J.; Maciel, R. S. P. (Advanced Information Systems Engineering Workshops. CAiSE 2012. Lecture Notes in Business Information Processing, 2012)
Automation is the essence of MDD (Model-Driven Development). Transforming models into models following a set of rules is at the core of automation. It allows using tools to enliven processes that have been defined. Transition methods are most likely the most important player in the engineering of software. The 4SRS (Four Step Rule Set) is a transition method we adopt in this paper to focus the discussion on the transition from the analysis to the design of software. It has been formalized as a small software development process that can be plugged into larger software development processes. That formalization was conducted with the SPEM (Software & Systems Process Engineering Metamodel), which is a process modeling language for the domain of software and systems. This paper exemplifies how a transition method like the 4SRS can be modeled with the SPEM as a way to study the benefits of the automatic or semiautomatic execution of a transition method as a small dedicated software development process.